2008
DOI: 10.1097/mej.0b013e3282f08aa4
|View full text |Cite
|
Sign up to set email alerts
|

Complications of heroin abuse

Abstract: A 21-year-old man presented to the emergency department in St James's Hospital by ambulance. He was found collapsed at home by his uncle. He was complaining of severe pain and swelling to his left lower limb, with reduced sensation to his left foot. He was hepatitis C positive from intravenous drug use, and had most recently used both heroin and cocaine 5 days previously on his release from prison. Musculoskeletal exam showed extensive swelling of his left lower limb, with tense calf compartments. Initial labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 9 publications
0
18
0
5
Order By: Relevance
“…These include cocaine, heroin, amphetamine, PCP and ETOH causing rhabdomyolysis and sometimes compression syndrome 36. The illicit drugs are almost always mixed with various agents.…”
Section: Common Drugs Inducing Muscle Toxicitymentioning
confidence: 99%
“…These include cocaine, heroin, amphetamine, PCP and ETOH causing rhabdomyolysis and sometimes compression syndrome 36. The illicit drugs are almost always mixed with various agents.…”
Section: Common Drugs Inducing Muscle Toxicitymentioning
confidence: 99%
“…Pavlovic et al (12) reported on 3 patients with acute infectious cellulitis who subsequently developed compartment syndrome. Other atraumatic causes that have appeared in studies such as case reports have included acute exercise (13,14), school sports activity in an adolescent male (10), gastrocnemius hematoma (15), rhabdomyolysis secondary to loss of consciousness with heroin abuse (16), muscle infraction secondary to microvascular disease (17), a tight or constricting cast, and those with no identifiable etiology (6).…”
Section: Discussionmentioning
confidence: 98%
“…Hastalar bu yakınmalar ile başvur-dukları sağlık merkezinde yapılan genel değerlendirme sırasında alınan anamnez ve laboratuvar tetkikleri sırasında böbrek fonksiyon testlerinde ve kas enzimlerinde yükseklik ile birlikte hastanın kendisi veya yakınlarının verdiği hastanın uyuşturucu kullandığını söylemesi ile tanı konur. Burada hastayı değerlendiren doktorun şüphelenmesi ve hasta veya yakınlarını uyuşturucu madde kullanımı konusunda özellikle sorgulaması önemlidir (9). Çoğu olguda klinik olarak tanı konur, böbrek biyopsisi nadiren gerekli olmaktadır (6 …”
Section: Discussionunclassified